On isometries satisfying deformed commutation relations - Ostrovska, O.; Yakymiv, R. Y. (Methods of Functional Analysis and Topology, 2019)
We consider an C^*-algebra E_1,n^q, q1, generated by isometries satisfying q-deformed commutation relations. For the case |q|